Recent applications of linear analysis techniques. - Gibbard, M.J.
This paper is based on material presented at the Panel Session: Recent Applications of Linear Analysis Techniques conducted during the 1998 IEEE PES Summer Meeting. The topics discussed include: control system design; system identification; large scale system applications; simultaneous coordination of power system stabilisers and FACTS controllers; robust power system stabilisation; small signal stability analysis based on time-domain identified models; EM transient studies modal analysis; and power system dynamics nonlinearities, normal forms method
Keywords: EM transient studies modal analysis; FACTS controllers; Control system design; Large scale system applications; Linear analysis techniques; Normal forms method; Power system dynamics nonlinearities; Power system stabilisers; Robust power system stabilisation; Small signal stability analysis; System identification; Time-domain identified models